2015
DOI: 10.1186/s12884-015-0711-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and mean arterial pressure in normotensive and chronic hypertensive pregnant women: a prospective, longitudinal study

Abstract: BackgroundBeing overweight is associated with both higher systolic blood pressure (SBP) and diastolic blood pressure (DBP) during pregnancy and increased risk of gestational hypertensive disorders. The objective of this study was to determine and quantify the effect of body mass index (BMI) on mean arterial pressure (MAP) at several time points throughout pregnancy in normotensive (NT) and chronic hypertensive pregnant (HT) women.MethodsA prospective longitudinal study was carried out in 461 singleton pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
4
8
0
2
Order By: Relevance
“…In this study, SBP and DBP were increased by 0.25 and 0.18 mm Hg per BMI unit, respectively. These findings were similar to those in a previous study 28 which reported an increased mean arterial pressure (MAP) of 0.21 mm Hg per BMI unit, but were smaller compared with another study 5 which reported the mean differences of blood pressure in the first, second and third trimesters of 1.03, 0.98 and 0.89 mm Hg for SBP per BMI unit and 0.83, 0.81 and 0.74 mm Hg for DBP per BMI unit. These discrepancies could be attributed to differences in variables included in the adjustment model, where in the latter study gestational weight gain was taken into account in the adjusted model but not in our analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, SBP and DBP were increased by 0.25 and 0.18 mm Hg per BMI unit, respectively. These findings were similar to those in a previous study 28 which reported an increased mean arterial pressure (MAP) of 0.21 mm Hg per BMI unit, but were smaller compared with another study 5 which reported the mean differences of blood pressure in the first, second and third trimesters of 1.03, 0.98 and 0.89 mm Hg for SBP per BMI unit and 0.83, 0.81 and 0.74 mm Hg for DBP per BMI unit. These discrepancies could be attributed to differences in variables included in the adjustment model, where in the latter study gestational weight gain was taken into account in the adjusted model but not in our analysis.…”
Section: Discussionsupporting
confidence: 93%
“…It was in accordance with the reports from previous studies. 5 14 15 28 Almost similar to our findings, a study which explored the relation between blood pressure during pregnancy with gestational age and pre-pregnancy BMI as continuous scale measurements also found that SBP and DBP levels generally increased with higher pre-pregnancy BMI at any gestational age. 16 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This effect was present consistently over the course of pregnancy, in accordance with the reports from previous studies. 8,20,21 Elevated pregnancy blood pressure associated with maternal pre-pregnancy BMI is also in accordance with a large body of literature that documents increased pre-eclampsia risk among overweight and obese women. 19,22,23 As a change in body composition and an accretion of water occurs differently in women during pregnancy, body weight gain might not be the best and only measure reflecting changes in fat storage.…”
Section: Discussionsupporting
confidence: 82%
“…Сложеност патофизиолошких дешавања огледа се у сазнању да хипертензивне особе могу да развију општи пад у бета-адренергичком одговору, који модулира развој гојазности у хипертензији. Сходно томе, претерана сим-патичка активација доводи до хипертензије и повећања телесне тежине, а даље повећање телесне тежине погор-шава хипертензију 31 . Сматра се да студије пресека дају реалније подат-ке од лонгитудиналних, јер није могуће да се директно процени утицај телесне тежине на крвни притисак на различитим нивоима крвног притиска и различитим ка-тегоријама гојазности 7 .…”
Section: душан M миљковић слађана з тодоровићunclassified